Ma’had-Based Management at Raden Fatah State Islamic University Palembang - Amna Idris Abdallah Khater; Ahmad Zainuri (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
This study explores the implementation of Ma’had-based management at Raden Fatah State Islamic University (UIN Raden Fatah) Palembang, Indonesia, as a model for integrating traditional Islamic values within modern higher education. The Ma’had system emphasizes spiritual development, moral discipline, and community living, offering a holistic alternative to conventional academic management. Through a literature review methodology, the research analyzes the core components, benefits, and challenges of this approach, particularly in its influence on students' academic performance and spiritual growth. Findings suggest that while Ma’had-based management fosters discipline, ethical behavior, and religious identity, it also poses challenges such as adaptation difficulties for students from non-pesantren backgrounds and coordination issues between academic and religious units. The study highlights the importance of institutional support, clear policies, and adaptive program structures in ensuring successful integration. This research contributes to the discourse on value-based education by demonstrating how Islamic traditions can harmoniously coexist with contemporary university governance, providing practical insights for other Islamic higher education institutions seeking to adopt similar models.